PENGARUH MODEL GAME BASED LEARNING DENGAN MEDIA DADU PANCASILA TERHADAP HASIL BELAJAR SISWA KELAS IV SD NEGERI 27 PALEMBANG - Vitalita, Erin; Handayani, Widya; Dedy, Adrianus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted based on the problem of students' low learning outcomes in Civic Education, particularly on the topic of Pancasila as the Values of Life, as well as the limited use of learning models that actively engage students. The purpose of this study was to determine the effect of the Game Based Learning model assisted by the Pancasila Dice media on the learning outcomes of fourth-grade students at SD Negeri 27 Palembang. This study employed a quantitative approach using an experimental method with a Posttest-Only Control Group Design. The research participants consisted of 35 fourth-grade students, including 17 students in Class IV.A as the control group and 18 students in Class IV.B as the experimental group. Data were collected through a learning outcomes posttest and analyzed using the Independent Samples t-test. The findings revealed that the experimental group achieved a higher mean posttest score (78.33) than the control group (60.59). Furthermore, the significance value (Sig. 2-tailed) was 0.001, which was lower than 0.05, indicating a statistically significant difference between the two groups. Therefore, it can be concluded that the implementation of the Game Based Learning model assisted by the Pancasila Dice media had a significant positive effect on students' learning outcomes. These findings suggest that this learning model can serve as an effective alternative for teachers to create more active, engaging, and meaningful learning experiences, thereby improving students' learning outcomes in Civic Education.